A process model for underground coal gasification – Part-II growth of outflow channel. (1st October 2016) - Samdani, Ganesh; Aghalayam, Preeti; Ganesh, Anuradda; Sapru, R.K.; Lohar, B.L.; Mahajani, Sanjay
Highlights: Proposed a compartment model for phase-II of UCG using actual on-field RTD studies. Integrated non-ideal flow patterns with spalling and detailed kinetics of the given coal. Good agreement with exit gas quality and coal consumed in laboratory experiments. Provided justification for the approach of modeling two phases of UCG, separately. Abstract: Underground Coal Gasification (UCG) is a process of gasifying coal in-situ to produce syn-gas. The gas thus produced, passes through the outflow channel that leads to the production well. As explained in part-I of this paper (Samdani et al., 2015), UCG can be divided in two distinct phases. The phase-I corresponds to initial vertical growth of the cavity and the output from phase-I model provides input to the phase-II model. This paper presents an unsteady state model for phase-II of UCG, wherein, the growth occurs in the horizontal direction towards the production well through the outflow channel. A compartment model, based on tracer studies performed on actual UCG cavity, is developed for phase-II of UCG. Here, the outflow channel is divided in small sections along the length, each consisting of rubble zone, void zone and roof at the top. This reduces the complexity caused by non-ideal flow patterns and changing sizes of different subzones inside the outflow channel. The subzones and the sections are linked appropriately, for mass and energy flow, to give overall performance of UCG. The proposed approach combines chemical reactions, heat and mass transfer effects, spalling characteristic and complex flow patterns to achieve meaningful results. In all, seven gas species, three solid species and eleven reactions are included. The simulation results such as variation in solid density, dynamics of different zones, exit gas quality are presented. The model is validated by comparing the predicted exit gas quality and that observed during similar laboratory scale experiments. Finally the results are also compared with pilot scale field-trials. This model along with the phase-I model provides a complete modeling solution for UCG process.